1979
DOI: 10.1063/1.438211
|View full text |Cite
|
Sign up to set email alerts
|

Exothermic rate restrictions on electron transfer in a rigid medium

Abstract: Many highly exothermic (2–3 eV) electron transfer reactions are shown to be slower than moderately exothermic reactions by factors as large as 105. The decrease occurs in a regular way with increasing exothermicity, tending to confirm theoretical predictions of Franck–Condon restrictions on strongly exothermic electron transfer reactions. Deviations from the above trends occur if the reaction product, a molecular anion, has a low-lying electronic excited state into which the reaction may occur with more modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
2

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(65 citation statements)
references
References 75 publications
3
60
0
2
Order By: Relevance
“…In their experimental studies of electron transfer in solid solutions, Miller et al 11,12 have shown that the results can be very well analyzed by assuming the following form for k(r).…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…In their experimental studies of electron transfer in solid solutions, Miller et al 11,12 have shown that the results can be very well analyzed by assuming the following form for k(r).…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…This possibility has received only limited discussion in the photosynthesis field (62) and in electron transfer work in general (63)(64)(65)(66). The simple concept is that the barrier height for electron tunneling may decrease with increasing dielectric constant, thereby increasing orbital overlap and enhancing the electronic coupling between reactant and product states (65,66).…”
Section: Analysis Of Band Shifts For the Monomeric Bchlsmentioning
confidence: 99%
“…[8][9][10][11] However, many systems predicted to exhibit inverted region behavior do not and have ET rates that exceed expected rates by orders of magnitude. 10,[12][13][14][15][16] One mechanism used to explain these deviations is the participation of excited states in the ET products, of either vibrational or electronic nature. 14,[17][18][19][20] Both effectively reduce the exergonicity of the ET process; the case of an electronically excited state is illustrated in Figure 1, in which the barrier can be bypassed by accessing an excited state of the radical anion of the acceptor, A• -*.…”
Section: Introductionmentioning
confidence: 99%